Problematic Issues of Guaranteeing Property and Personal Non-Property Rights of Victims within Criminal Proceedings - O. O. Yukhno (Law and Safety)
The problematic issues of guaranteeing compensation of property and personal non-property rights (moral damage) to victims within criminal proceedings have been studied. The author has analyzed international and legal acts, national criminal, criminal procedural and civil legislation, law-enforcement and court practice generalized by the Supreme Court of Ukraine concerning the legal bases and procedural duty of guaranteeing the civil claim to the victim within criminal proceedings by the interrogator, investigator and prosecutor, when the victim suffered material and moral damage caused by the crime and misdemeanor. The author has studied the issue of the genesis and introduction into the national criminal procedural legislation of the provisions on guaranteeing and implementing personal non-property rights (moral damage) by victims. A number of inconsistencies, gaps and shortcomings of the current criminal, criminal procedural and civil legislation on the specified issues, in particular taking into account the existing new market legal relations in society, which prevents effective and reliable compensation for damage to both individuals and legal entities. On this basis, the author has provided specific suggestions and recommendations for its improvement. The scientific views of scholars and representatives of scientific schools on theoretical issues, the existing legal and procedural mechanism for compensation for material and moral damage to the victim within criminal procedure of Ukraine, as well as on determining the definition of “providing compensation to the victim”. The author of the article has presented own vision of the specified problematic issues.